Comparison of surgical outcomes of endoscopic enucleation of the prostate using different energies - Hyun Ju Jeong; Hyeji Park; Steffi Kar Kei Yuen; Christine Joy Castillo; Seung-June Oh; Sung Yong Cho (Therapeutic Advances in Urology)
Objective: This study evaluates surgical outcomes in benign prostatic hyperplasia (BPH) patients undergoing transurethral enucleation using various holmium laser (HoLEP) settings and/or bipolar devices (BipoLEP). Design: This study was retrospective. Methods: We retrospectively analyzed 158 BPH patients treated surgically, categorized by method: BipoLEP ( n  = 28), HoLEP with short pulse (HoLEP-SP, n  = 26), HoLEP with long pulse and low energy (HoLEP-LP/LE, n  = 29), HoLEP with long pulse and high energy (HoLEP-LP/HE, n  = 26), HoLEP using Moses technology (HoLEP-Mo, n  = 19), and a combination of HoLEP and BipoLEP (HoLEP-mix, n  = 30). We assessed enucleation, morcellation, coagulation, and overall operation efficiency, along with complications at immediate, 2-week, and 3-month postoperative intervals. Results: The HoLEP-LP/LE group exhibited the highest overall operation efficiency ( p  < 0.05). The BipoLEP and HoLEP-SP groups had lower enucleation efficiency ( p  < 0.05). HoLEP-LP/LE and BipoLEP showed superior coagulation efficiency ( p  < 0.05). Excluding hard nodule cases, the HoLEP-mix group had reduced morcellation efficiency compared to HoLEP-LP/LE ( p  < 0.05). Complication rates did not significantly differ between groups ( p  > 0.05). Conclusion: The HoLEP-LP/LE procedure demonstrated superior performance in enucleation, morcellation, coagulation, and overall operation efficiency. Complication rates were comparable across all groups. BipoLEP, while less efficient in enucleation than some HoLEP settings, proved effective and safe. In addition, the Moses technology may offer enhanced bleeding control.